Fortnightly variability of horizontal salinity gradient affects exchange flow in the Sumjin River estuary - Cho, Eun-Byeol; Tak, Yong-Jin; Cho, Yang-Ki; Na, Hanna (Frontiers in Marine Science, 2022)
The horizontal salinity gradient has been reported to play a crucial role in fortnightly variability of estuarine exchange flow in short estuaries. However, spatiotemporal variations in the salinity gradient and exchange flow have not been examined over an entire short estuary, as only data observed only at specific points was available. We analyzed the variation in salinity gradient along the entire Sumjin River estuary and its effect on the exchange flow over fortnightly tidal cycles based on observations and numerical model experiments. The salinity gradient and exchange flow were in different phases between the lower and upper estuaries by 6–7 days. The maximum salinity gradient periodically reciprocated along the channel as a result of salt flux changes determined by vertical mixing. The stronger exchange flow (> 0.04 m s-1) changed location from mouth to head of estuary while the tidal range decreased, resulting from variability of the salinity gradient. The horizontal salinity gradient is large enough to overwhelm the vertical mixing effect on the exchange flow. The spatiotemporal changes of strong exchange flow correspond well with the horizontal Richardson number value (> 3). This study suggests that for the health of estuarine ecosystems, it is important to determine the spatiotemporal variation in exchange flow throughout the estuary.